A day in the life of an aged cat – Environment of old domestic cats and welfare implications - Sara Hoummady; Oriana Rameau; Audrey Besegher; Thierry Bedossa; Sarah Jeannin; Pauline-M Anton; Yohan Stephan; Nancy Rebout; Morgane Robles (Journal of Veterinary Behavior, 2026)

Personality traits of aged dogs according to their cognitive status - Audrey Besegher; Sarah Jeannin; Nancy Rebout; Tiphaine Blanchard; Samanta Świerk; Yohan Stephan; Caroline Gilbert; Morgane Robles; Thierry Bedossa; Sara Hoummady (Applied Animal Behaviour Science, 2025)

Oxygenated Liquid Organic Hydrogen Carrier (oxo-LOHC) systems: The biodegradation and endocrine disrupting potential of oxo-LOHCs, intermediates and transformation products - Yohan Seol; Marta Markiewicz; Viktor Schmalz; Stephan Beil; Chantal Martin; Peter Wasserscheid; Stefan Stolte (Journal of Hazardous Materials, 2025)

Aquatic toxicity, bioaccumulation potential, and human estrogen/androgen activity of three oxo-Liquid Organic Hydrogen Carrier (oxo-LOHC) systems - Yohan Seol; Marta Markiewicz; Stephan Beil; Sara Schubert; Dirk Jungmann; Peter Wasserscheid; Stefan Stolte (Journal of Hazardous Materials, 2024)

Continental mapping of forest ecosystem functions reveals a high but unrealised potential for forest multifunctionality - Fons van der Plas; Sophia Ratcliffe; Paloma Ruiz‐Benito; Michael Scherer‐Lorenzen; Kris Verheyen; Christian Wirth; Miguel A. Zavala; Evy Ampoorter; Lander Baeten; Luc Barbaro; Cristina C. Bastias; Jürgen Bauhus; et al. (Ecology Letters, 2018)
Humans require multiple services from ecosystems, but it is largely unknown whether trade‐offs between ecosystem functions prevent the realisation of high ecosystem multifunctionality across spatial scales. Here, we combined a comprehensive dataset (28 ecosystem functions measured on 209 forest plots) with a forest inventory dataset (105,316 plots) to extrapolate and map relationships between various ecosystem multifunctionality measures across Europe. These multifunctionality measures reflected different management objectives, related to timber production, climate regulation and biodiversity conservation/recreation. We found that trade‐offs among them were rare across Europe, at both local and continental scales. This suggests a high potential for ‘win‐win’ forest management strategies, where overall multifunctionality is maximised. However, across sites, multifunctionality was on average 45.8‐49.8% below maximum levels and not necessarily highest in protected areas. Therefore, using one of the most comprehensive assessments so far, our study suggests a high but largely unrealised potential for management to promote multifunctional forests.